MODIFICATION OF HETEROGENEOUS CATION-EXCHANGE MEMBRANE WITH ZNO-PDA PARTICLES FOR VANADIUM REDOX FLOW BATTERY - Yulanda, Nanda
Heterogenous ion exchange membranes usually have lower electrochemical characteristics than homogen structures. However, heterogeneous membranes are easier to fabricate and have better mechanical strength. In this study, heterogenous cation exchange membrane made of polypropylene and powdered cation exchange resin (Amberlite IR A120 Na) was modified with ZnO-Polydopamine (ZnO-PDA) particles. This study aims at determining effect of ZnO-PDA addition and cation exchange resin content on membrane characteristics. The membrane characteristics including water uptake (WU), water contact angle (WCA), ion-exchange capacity (IEC), proton conductivity, water permeability, and vanadium permeability were analyzed. The results of the study showed that WU, IEC, proton conductivity, water permeability, and vanadium permeability incresed with the ion exchange resins content. Meanwhile, the increasing ion exchange resins content decreased WCA valuee. In general, the introduction of ZnO-PDA into the membrane matrix leads to the opposite trends. It has been proved that the addition of ZnO-PDA could successfuly decrease vanadium permeability (ZnO-PDA 10%-b; 9.2×10-6 cm2/min) and water permeability (ZnO-PDA 10%-b; 0.66 L/m2.h.bar) required in the vanadium redox flow battery.